Analisis Upaya Perlindungan Hukum Bagi Anak Korban Pelecehan Seksual Di Kota Padang (Studi Terhadap Putusan No.30/PID.SUS-ANAK/2021/PN PDG) - Kharisma Bunga Leony; Sry Wahyuni; Desi Sommaliagustina (CV. ITTC INDONESIA, 2024)
Sexual abuse of children is one of the serious problems faced by the current government because it is related to the government's efforts to implement Law No. 35 of 2014 concerning Child Protection. On the other hand, children who are victims of sexual abuse are part of society that has not yet developed both physically and psychologically so they need special companions in their handling. The problems in this study are focused on how to form law enforcement and legal protection for childrens victims of sexual abuse in Padang City. The purpose of this study is to find out how law enforcement efforts and legal protection against the crime of sexual abuse of children are made. Therefore, this type of research is normative legal research because this study discusses decision No.30/PID. SUS-ANAK/2021/PN PDG. Based on the results of the discussions that have been carried out, it can be concluded that in the decision there are still shortcomings in ensuring the recovery and rehabilitation of children as a whole. In addition, the ruling does not appear to have fully considered the long-term impact that children may experience, as well as the lack of a comprehensive approach to protecting children's rights in accordance with the principle of best interests of the child. The less comprehensive approach and limited education and mentoring programs for children show that the legal protection provided is still not optimal. This process includes complaints, investigations by the police, investigations by prosecutors, trials in special children's courts, and protection during legal proceedings and after court decisions. This effort aims to ensure that victims get the justice and protection they deserve.